2009
DOI: 10.4103/0028-3886.53272
|View full text |Cite
|
Sign up to set email alerts
|

Surgical considerations for ′intrinsic′ brainstem gliomas: Proposal of a modification in classification

Abstract: The surgical management of intrinsic brainstem tumors presents a surgical challenge; radical excision yielded a good outcome in the majority of cases. The authors propose a classification system for 'intrinsic' brainstem tumors for defining surgical strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 27 publications
1
8
1
Order By: Relevance
“…6,14,17,22 Many investigators have advocated resection as the primary treatment for focal brainstem tumors. 3,9,11,15,16,18,20,21,23,24,27 Some researchers have found that the extent of resection is an important prognostic factor for survival, contrary to our findings. 16,24,25 …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…6,14,17,22 Many investigators have advocated resection as the primary treatment for focal brainstem tumors. 3,9,11,15,16,18,20,21,23,24,27 Some researchers have found that the extent of resection is an important prognostic factor for survival, contrary to our findings. 16,24,25 …”
Section: Discussioncontrasting
confidence: 99%
“…26 Many classification systems have been proposed, incorporating features such as size, location, and imaging characteristics. 1,21,23,26 Epstein and McCleary 8 grouped intrinsic nonexophytic tumors as focal (circumscribed mass > 2 cm in diameter without associated edema), diffuse, or cervicomedullary. Choux et al 5 described 4 types of tumors: Type I, diffuse brainstem gliomas; Type II, focal intrinsic tumors (solid or cystic); Type III, exophytic; and Type IV, cervicomedullary.…”
mentioning
confidence: 99%
“…These results are consistent with other studies that have patients with these diffuse intrinsic brainstem gliomas experiencing poor prognosis and survival outcomes of < 10% at 2 years in some cases [29]. Pilocytic astrocytomas tend to have much better outcomes with lower recurrence rates and a less aggressive invasion of the surrounding parenchyma [15]. …”
Section: Discussionsupporting
confidence: 82%
“…It is possible that more aggressive surgical measures were necessary given the malignant nature of these tumors possibly explaining our nonsignificant finding with regards to tumor extension versus focal location. Radical excision of the neoplasm is often the preferred method of surgery in most cases as partial resection is associated with relatively high recurrence rates (up to 20% in some cases) [15]. In cases where surgery is not performed, it is often at the discretion of the performing surgeon who anticipates possible severe complications or dangerous surgical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[2526] Damage to the lower cranial nerves leads to dysphagia, absent gag and cough reflexes. [272829] These individuals are at risk for frequent micro aspirations and hence when indicated tracheostomy with PEG/Ryles tube feeding is recommended. Post-operative respiratory compromise is a serious issue and was observed in twelve of our patients.…”
Section: Discussionmentioning
confidence: 99%